2019
DOI: 10.5120/ijca2019918672
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning based Marks Prediction to Support Recommendation of Optimum Specialization and Study Track

Abstract: Due to the spread of educational management information systems (EMIS), it become necessary to add intelligent layers to improve the educational process. One of the important tasks when the student moves from one stage to the other within the educational system of a university is the determination of the appropriate department if the transition is from the first level of a faculty to a certain department or the determination of the specialization track within a certain department in higher levels. These transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…They found that the neural network (NN) outperformed the other approaches with a classification accuracy of 86.72%, the sensitivity of 0.92, specificity of 0.82, and MCC of 0.72. Abosamra et al [56] examined various types of ML predictions models on a dataset, which gave the best choice as a (NN) architecture that provides 6.26 an average root mean squared error, and a mean absolute error of 5.74 based on a scale of 0 to 100.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that the neural network (NN) outperformed the other approaches with a classification accuracy of 86.72%, the sensitivity of 0.92, specificity of 0.82, and MCC of 0.72. Abosamra et al [56] examined various types of ML predictions models on a dataset, which gave the best choice as a (NN) architecture that provides 6.26 an average root mean squared error, and a mean absolute error of 5.74 based on a scale of 0 to 100.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It transforms the possibly correlated features into linearly uncorrelated features [34]- [36]. It can be described using the following steps: 1) Perform data standardization which means the values of each feature in the data are given a zero-mean and unit-variance through feature standardization [37]. It has a significant effect on PCA.…”
Section: ) Feature Extraction Using Cnn From Raw Datamentioning
confidence: 99%
“…A combination of the decision tree and Neural Network approaches has been applied in different studies. For example, a new RS was built to predict specialization and study track for students based on grades [12]. Adding the Neural Network and decision tree provides better results with a small accuracy difference.…”
Section: Literature Reviewmentioning
confidence: 99%